2020
DOI: 10.1021/acs.est.9b06932
|View full text |Cite
|
Sign up to set email alerts
|

Global Ocean Spectrophotometric pH Assessment: Consistent Inconsistencies

Abstract: Ocean acidification (OA)or the decrease in seawater pH resulting from ocean uptake of CO2 released by human activitiesstresses ocean ecosystems and is recognized as a Climate and Sustainable Development Goal Indicator that needs to be evaluated and monitored. Monitoring OA-related pH changes requires a high level of precision and accuracy. The two most common ways to quantify seawater pH are to measure it spectrophotometrically or to calculate it from total alkalinity (TA) and dissolved inorganic carbon (DIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 97 publications
(203 reference statements)
2
40
0
Order By: Relevance
“…erage (Álvarez et al, 2020;Carter et al, 2018). Outside the North Pacific, we believe, therefore that the pH data are consistent to 0.01.…”
Section: Ph Scale Conversion and Quality Controlsupporting
confidence: 51%
See 3 more Smart Citations
“…erage (Álvarez et al, 2020;Carter et al, 2018). Outside the North Pacific, we believe, therefore that the pH data are consistent to 0.01.…”
Section: Ph Scale Conversion and Quality Controlsupporting
confidence: 51%
“…3.2.5). Recent literature has demonstrated that internal consistency evaluation procedures are subject to errors owing to incomplete understanding of the thermodynamic constants, major ion concentrations, measurement biases, and potential contribution of organic compounds or other unknown protolytes to alkalinity (Takeshita et al, 2020), which lead to pH-dependent offsets in calculated pH (Álvarez et al, 2020;Carter et al, 2018): these may be interpreted as biases and generate false corrections. The offsets are particularly strong at pH levels below 7.7, when calculated and measured pH are different by on average between 0.01 and 0.02 units.…”
Section: Ph Scale Conversion and Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Spatiotemporal mismatch between sensor and bottle sampling adds to uncertainty in independent validation (Bresnahan et al 2014; McLaughlin et al 2017) and a comprehensive discrete sampling program can be painstaking and expensive. Discrete measurements of the marine inorganic carbon system have been refined for decades (Dickson et al 2007; Millero 2007; Riebesell et al 2010); recent work has scrutinized various techniques, uncovering small but measurable effects on pH accuracy from dye impurities as well as a pH‐dependent discrepancy between pH measured spectrophotometrically and estimated from total alkalinity and dissolved inorganic carbon measurements (Liu et al 2011; Carter et al 2018; Fong and Dickson 2019; Álvarez et al 2020; Takeshita et al 2020 a ). All of these issues contribute to increased uncertainty in the pH sensor data and create substantial hurdles in the pursuit of stringent community standards, such as the climate quality goal.…”
mentioning
confidence: 99%